Optimising the mixing proportion of solidified landfill waste for sustainable reuse in paving block construction. (2015) - Hoque, M.A.; Haque, M. Aminul
The study optimises the mixing proportion for solidified landfill waste confirming the immobilisation of heavy metal in the waste matrix. Paving blocks were constructed for compressive strength and leachate behaviour analysis. The study revealed the mixing proportion of 1:2 for paving block construction was found to be optimum providing a satisfactory compressive strength of 2, 748 psi after 28 days curing period. In addition, cumulative leaching concentrations of Fe, Cu and Ni from the same proportioned solidified blocks were found to be 1.203 mg/l, 0.157 mg/l and 0.493 mg/l respectively along with the nominal rate of release of heavy metals after 28 days of curing period by ensuring the encapsulation of heavy metals in the solidified matrix. The outcome of the study will be potential solution to treat and recycle the harmful wastes as construction materials like paving blocks, river bank protection materials, road construction materials, etc., using S/S techniques.